Analisis Kualitas Pelayanan Sekolah SMAN 1 Berastagi terhadap Kepuasan Siswa dengan Metode Importance Performance Analysis (IPA) - Gopinda Surbakti; Asima Manurung; Muhammad Romi Syahputra; Mardiningsih Mardiningsih (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
In improving the quality of service to provide satisfaction to students, SMAN 1 Berastagi needs efforts to meet student expectations, so that students get satisfaction with the services provided by SMAN 1 Berastagi. Student satisfaction with the quality of services received can be measured using Importance Performance Analysis (IPA). Physical evidence, dependability, responsiveness, assurance, and care are the five aspects of service quality that make up service quality, which is an important term for service consumers. Of the 20 attributes asked to students, there are 2 attributes that are in the A quadrant important and anticipated. Prioritizing improvements in this dimension needs to be done. Factors included in quadrant A include ease of access to school services and ease of contact for educators.